Detail of supporting brackets - Ghosh, Ayan (2023)
Detail of brackets inside the BMC building. These were inspired from Hindu temple architecture. The amalgamation of Hindu and Islamic architectural details with the overall Gothic style was a delicate and gradual process which Frederick Stevens successfully managed to balance, thereby guaranteeing his pre-eminence in this style during the zenith of Bombay Gothic architecture.